PENGARUH MEREK, DESAIN PRODUK DAN LOKASI TERHADAP MINAT BELI KONSUMEN PADA PERSEBAYA STORE GRESIK - Susanto, Aris (Universitas Muhammadiyah Gresik, 2019)
The purpose of this study was to determine the effect of brand, product design and location on consumer buying interest in Persebaya Store Gresik. The sample uses a non probability sampling method with a purposive sampling or random sampling procedure by selecting 100 visitors. The data analysis technique uses multiple linear regression. The results of multiple linear regression analysis prove that the brand and location proved not to have a significant effect partially on consumer buying interest in Persebaya Store Gresik, while product design proved to have a partially significant influence on consumers' buying interest in consumer buying interests at Persebaya Store Gresik. Simultaneously the brand, product design and location proved to have a significant effect on consumers' buying interest in Persebaya Store Gresik.